LEGAL RESPONSIBILITY FOR MEDICAL ERROR - Savchenko, V.A. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine", 1970)
Responsibility of medical workers has set of nuances. In the legislation of Ukraine many questions connected with the given theme are not opened. In the certain measure, the given problematics is studied by criminal law, but administrative and especially civil sphere of law contains set of legal blanks. Feature of regulation of a question of responsibility of medical workers consists that they are special subjects правоотношений so possess the special rights and duties, their status is separately considered by the legislator. In a context of understanding of medical workers as special subjects law it is necessary to consider questions on their legal responsibility.